Corneal endothelium of the Magellanic penguin (Spheniscus magellanicus) by scanning electron microscopy - Pigatto, João A. T.; Laus, José L. [UNESP]; Santos, Jaime M. [UNESP]; Cerva, Cristine; Cunha, Luciana S.; Ruoppolo, Valéria; Barros, Paulo S. M. (American Association of Zoo Veterinarians, 2005)
The corneal endothelium is essential for the maintenance of the corneal transparency. The aim of this study was to examine the morphology of the endothelial surface and perform morphometric analysis of the normal corneal endothelial cells of the Magellanic penguin (Spheniscus magellanicus) using scanning electron microscopy. The present work demonstrates that the corneal endothelium of the Magellanic penguin is similar to those described in other vertebrates. Copyright 2005 by American Association of Zoo Veterinarians.
Keywords: Corneal endothelium; Magellanic penguin; Morphometric analysis; Scanning electron microscopy; Spheniscus magellanicus; animal; animal disease; cornea epithelium; cytology; histology; methodology; penguin; scanning electron microscopy; ultrastructure; Animals; Epithelium, Corneal; Microscopy, Electron, Scanning; Spheniscidae; Vertebrata